English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

can you please help ASAP! im taking algebra ! help me!

2006-11-28 15:55:38 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

x^2 - 2(3-x^2)
Distribute the -2
x^2 + (-2)(3) + (-2)(-x^2)
Simplify
= x^2 - 6 + 2x^2
Combine like terms
= 3x^2 - 6

2006-11-28 15:57:33 · answer #1 · answered by MsMath 7 · 1 0

1

2006-11-28 23:57:35 · answer #2 · answered by Dead Dog 2 · 1 0

This is just a simplification. In which case, all you have to do is expand and then group like terms.

x^2 - 2(3 - x^2) first, multiply the 2 with the bracketed terms. In this case, it's a -2, so be sure to multiple -2 with the bracketed terms because the minus sign matters in this case.

x^2 -6 + 2x^2

Now, group together the x^2's.

3x^2 - 6

That's it!

2006-11-28 23:59:17 · answer #3 · answered by Puggy 7 · 1 0

If your original question is exactly written like this: x²-2(3- x²)

Then
x²-2(3- x²), distribute -2 to the binomial (3- x²)
x² - 6 + 2x², combine like terms
3x² - 6.

2006-11-29 00:00:48 · answer #4 · answered by MrDanaH 2 · 1 0

x^2-6+2x^2
x^2+2x^2=3x^2-6=0
-6=0
3x^2=0
0/3=0
sq root of 0= 0 therefore x=0 and x=-6

2006-11-29 00:00:21 · answer #5 · answered by krazee_wetblack 1 · 1 0

fedest.com, questions and answers